Proceedings of the Third International Symposium, SEUSL: 6-7 July 2013, Oluvil, Sri Lanka - Vasanthakumar, S.; Thirukkumaran, G.; Arulnandhy, V. (Proceedings of the Third International Symposium,Oluvil, Sri Lanka, 2013)
Genetic diversification based on morphological attributes in sesame grown in Jaffna district was critically examined in this study. The results showed that, seed number is positively correlated with number of carpels in sesame capsule. Higher seed number was obtained in four carpel (82.06) and five carpel (84.94) types, Multilocules and multicapsules of the sesame are the major attributes to increase the yield. However, five carpel and six carpel capsule contain sesame cultivar are not recommended yet in India or Sri Lanka.
Keywords: Sesame; Multicapsule; Multilocule; Carpel Type; Locule Number